Cannabis farms in California rely on wells outside of regulated groundwater basins. (21st July 2021) - Dillis, Christopher; Butsic, Van; Carah, Jennifer; Zipper, Samuel C; Grantham, Theodore
Abstract: As permitted cannabis farming in California continues to expand statewide, including in ecologically sensitive watersheds, an improved understanding of water-use practices is needed. Existing evidence suggests widespread reliance on groundwater wells for cannabis irrigation may result in streamflow depletion, yet our understanding of where and why well use for cannabis is most prevalent is currently limited. Here, we use California state cannabis permitting data to address four important information gaps regarding well use by cannabis farming: (1) the prevalence of groundwater wells as an irrigation source for regulated cannabis farms statewide, (2) the extent to which groundwater use occurs outside of regulated groundwater basins, (3) the most useful predictors of whether a farm will rely on groundwater for irrigation, and (4) the potential well use from cannabis farms that are currently unpermitted. Well use by cannabis farms is common statewide, with percentages in excess of 75% among permitted farms in nine of the 11 top cannabis producing counties. In eight of these 11 counties, more than one quarter of farms using wells are located outside of groundwater basins subject to state groundwater use regulations. We found that cultivation area size was a positive predictor of well use, while annual precipitation and on-farm stream network density were negative predictors, highlighting the influences of water demand and surface water availability. The output of a machine learning model trained with data from permitted farms in Northern California suggests that the majority (60%) of unpermitted farms are likely to use groundwater wells if they follow the same patterns as the regulated industry. Our results suggest that proactive steps be taken to address groundwater use in cannabis regulations in California and call for further research into the effects of groundwater use on streamflow, especially outside of large groundwater basins.